ECONOMIC EVALUATION OF INTERVENTIONS TO IMPROVE THE SAFE MOVEMENT OF TRAINS - Shevchenko, V. V.; Hnennyi, O. M. (Science and Transport Progress, 2009)
The methodical approach to an estimation of direct effect from investments into actions on increase of train traffic safety, which is defined as reduction of the risk level connected with train operation, due to the introduction of actions is developed. The risk level is defined on the basis of modelling density of distribution of quantity of transport accidents by their types during the year and an estimation of expectations of harm levels (economic, social, ecological) from each type of transport accidents. The method of definition of an economic evaluation of social aftermaths of a transport accident is offered.